Implementation of the Merdeka Belajar Curriculum in Islamic Religious Education Learning at SD Negeri 2 Bone-Bone, Grade IV A - Wahyuli Wahyuli; Maudin Maudin; Rusli Rusli; Abdul Rahim (Journal of Innovative and Creativity, 2025)
This study aims to describe the implementation of the Merdeka Belajar Curriculum in Islamic Religious Education (PAI) learning at SD Negeri 2 Bone-Bone and to identify the challenges and solutions encountered during the process. The background of this research is based on the shift in the national education paradigm, which emphasizes learning freedom, active student participation, and character development through the Profil Pelajar Pancasila (Pancasila Student Profile). This research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The subjects of the study include the Islamic Religious Education teacher and Grade IVA students. The findings indicate that the implementation of the Merdeka Curriculum in PAI learning has been carried out with adjustments based on local context and student needs. However, several obstacles remain, such as limited teacher training, lack of understanding of instructional tools, and challenges in learning assessment. Solutions include internal teacher training, the use of digital learning resources, and enhanced collaboration between teachers and students. This study is expected to contribute to the development of effective Islamic Religious Education teaching practices in the era of the Merdeka Curriculum.